EXAMINING THE USE OF QUILLBOT IN FACILITATING EFL STUDENTS’ ACADEMIC WRITING AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM STATE ISLAMIC UNIVERSITY OF MATARAM - Fifi Fazila; Muhsinin; Soni Ariawan (Journal of English Education and Literature, 2025)
This ponder points to investigate the recognitions and challenges confronted by EFL understudies in utilizing QuillBot as an scholastic composing instrument. QuillBot, as an counterfeit insights (AI)-based device, gives different highlights such as summarizing, linguistic use checking, and summarizing, which have the potential to move forward students' scholarly composing abilities. A subjective approach with case ponders was utilized in this investigate, with information collection through surveys and semi-structured interviews with 33 understudies of the English Instruction Ponder Program at the State Islamic College of Mataram. The comes about of the ponder demonstrate that most understudies have a positive discernment of QuillBot, especially in terms of ease of get to, change in composing quality, time effectiveness, and expanded certainty in composing. Be that as it may, challenges such as specialized impediments, reliance on the device, and the precision of rewording comes about were too distinguished. This considers gives imperative suggestions for the integration of AI innovation in English dialect learning and empowers the execution of educating methodologies that adjust mechanical help with the improvement of students' free aptitudes.